Improvement of the Safety Profile of Canaloplasty and Phacocanaloplasty: A Review of Complications and Their Management - Joanna Konopińska; Zofia Mariak; Marek Rękas (Journal of Ophthalmology)
Research on the methods used to achieve persistent and safe control of intraocular pressure resulted in the implementation of novel surgical procedures, such as canaloplasty and phacocanaloplasty. Herein, we review the literature focused on the safety profile of canaloplasty and phacocanaloplasty and the management of related complications. The aim of canaloplasty is to restore the natural aqueous outflow. This goal is achieved via a surgical procedure that involves viscocanalostomy with catheterisation of Schlemm’s canal (360°) and placement of a circumferential suture that tensions the canal walls. This improves Schlemm’s canal drainage, choroidoscleral flow, and subconjunctival filtration. The efficacy of canaloplasty for reducing the intraocular pressure is similar to those of trabeculectomy with mitomycin C and deep sclerectomy augmented with an implant and mitomycin C. However, canaloplasty is associated with a lower complication rate than those conventional techniques. Novel microsurgical techniques for the treatment of glaucoma are unlikely to replace the conventional methods. However, these new techniques offer alternatives, especially for patients who have an early indication for surgical intervention. Nevertheless, canaloplasty is associated with the expectations of efficient, safe, and modern surgical treatment.